The Role of Hypertonic Saline in Managing Malignant Cerebral Edema Due to Large Vessel Occlusion Stroke: A Case Report - Zairinal, Ramdinal Aviesena; Malutfi, Chandrika Najwa; Hidayati, Diah Balqis Ikfi (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Malignant cerebral edema (MCE) is a complication of large vessel occlusion stroke mainly treated by decompressive craniectomy. The aim of this case report is to demonstrate the efficacy of providing hypertonic saline (3% NaCl) as an alternative treatment for reducing intracranial pressure (ICP) in an MCE patient who refuses surgery. Case Presentation: A 66-year-old man went to the emergency department with unconsciousness, right-sided hemiplegia, and global aphasia for 4.5 hours before admission. His National Institutes of Health Stroke Scale (NIHSS) score was 12. The patient’s brain magnetic resonance imaging (MRI) revealed a large infarction on the left frontotemporoparietal lobe which caused a subfalcine herniation 1.4cm to the right side. He also suffered hyponatremia (115mmol/L). The family refused decompressive craniectomy. The patient received 200ml of 3% NaCl drip intravenous as an initial dose over 20 minutes every 6 hours. Subsequent administration is gradually reduced every 25ml with a distance adjusted to the patient’s condition up to 50ml as the last dose. The patient’s 90-day modified Rankin Scale (mRS) score was 4. Results: The patient with MCE in this case who was administered 3% NaCl as conservative therapy had satisfactory outcomes, as demonstrated by the improvement of the clinical neurological condition. Conclusion: In patients who decline surgery, 3% NaCl might be given as a conservative treatment option to reduce ICP while maintaining serum sodium levels under control. This case revealed a positive clinical result without complications.